2022
DOI: 10.1186/s13014-022-02083-6
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced NSCLC: a plea for sparing the ipsilateral normal lung—prospective, clinical trial with DART-bid (dose-differentiated accelerated radiation therapy, 1.8 Gy twice daily) by VMAT

Abstract: Background In radiation treatment of locally advanced non-small cell lung cancer (LA-NSCLC), ‘margins’ from internal target volumes to planning target volumes in the range of 12 to 23 mm are reported, and avoiding exposure of the contralateral lung is common practice. We investigated prospectively an approach with tight margins (7 mm) and maximal sparing of the ipsilateral normal lung. Mature results for the first endpoint (pneumonitis) and further toxicities are reported. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Historically, the radiation dose for SCLC has been 40–50 Gy either once a day (QD) or twice a day (BID). However, the INT-0096 clinical trial showed that most patients may relapse and suggested the need for an additional 60 Gy QD [ 19 , 21 , 22 , 23 , 24 ]. Conventionally, in both NSCLC and SCLC, the treatment regimen of 2 Gy QD typically leads to the application of a RF RT plan of approximately 40–44 Gy in 20–22 fractions.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the radiation dose for SCLC has been 40–50 Gy either once a day (QD) or twice a day (BID). However, the INT-0096 clinical trial showed that most patients may relapse and suggested the need for an additional 60 Gy QD [ 19 , 21 , 22 , 23 , 24 ]. Conventionally, in both NSCLC and SCLC, the treatment regimen of 2 Gy QD typically leads to the application of a RF RT plan of approximately 40–44 Gy in 20–22 fractions.…”
Section: Discussionmentioning
confidence: 99%